Ferrater Mora: political ideas - Terricabras, Josep-Maria (Journal of Catalan Intellectual History, 2014)
This paper proposes that although Ferrater Mora was never militantly political, his writing reveals an enduring interest in the relationship between Europe, Spain and Catalonia and a belief that their relations should adopt a federal design. The paper also examines Ferrater Mora’s opinions and feelings about the Catalan language beyond the use of it his circumstances obliged him to make. key words Josep Ferrater Mora, politics.